A primer on the dollar in the world economy : United States balance of payments and international monetary reform - Stevens, Robert Warren (New York : Random House, 1972)
The book deal with international economic relations as it concerns balance of trade. It also highlights the role international monetary fund in ensuring international monetary cooperation.
usc 26/05/17
Loans
Keywords: Balance of payments; International economic relations; International finance